Protocol refinement for a diabetes pragmatic trial using the PRECIS-2 framework - Russell E. Glasgow; Dennis Gurfinkel; Jeanette Waxmonsky; Jenny Rementer; Natalie D. Ritchie; Jennifer Dailey-Vail; Patrick Hosokawa; L. Miriam Dickinson; Bethany M. Kwan (BMC, 2021)
Abstract Background This report describes how we refined a protocol for a pragmatic comparative effectiveness study of two models of an evidence-based diabetes shared medical appointment intervention and used the PRECIS-2 rating system to evaluate these adaptations. Methods We report primary data collected between June and August 2019, and protocol refinements completed between 2018 and 2020. Twenty-two members of the study team collaborated in protocol refinement and completed the PRECIS-2 ratings of study pragmatism. We discuss study design refinements made to achieve the desired level of pragmatism vs. experimental control for each of the nine PRECIS-2 dimensions. Study team members received training on PRECIS-2 scoring and were asked to rate the study protocol on the nine PRECIS-2 dimensions. Ratings were compared using descriptive statistics. Results In general, the PRECIS-2 ratings revealed high levels of pragmatism, but somewhat less pragmatic ratings on the categories of Delivery and Organization (costs and resources). This variation was purposeful, and we provide the rationale for and steps taken to obtain the targeted level of pragmatism on each PRECIS-2 dimension, as well as detail design changes made to a) make the design more pragmatic and b) address COVID-19 issues. There was general agreement among team members and across different types of stakeholders on PRECIS-2 ratings. Conclusions We discuss lessons learned from use of PRECIS-2 and experiences in refining the study to be maximally pragmatic on some dimensions and less so on other dimensions. This paper expands on prior research by describing actions to achieve higher levels of pragmatism and revise our protocol fit to the changed context. We make recommendations for future use of PRECIS-2 to help address changing context and other strategies for the planning of and transparent reporting on pragmatic research and comparative effectiveness research. Trial registration Clinicaltrials.gov Registration ID: NCT03590041 .